PENERAPAN TEORI BELAJAR BEHAVIORISTIK DALAM PEMBELAJARAN PAI DI SDN NOGOPURO YOGYAKARTA - Muhammad Fadhil Alghi Fari Majid; Suyadi Suyadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Behavioristic theory is a theory that emphasizes changes in individual behavior at a better level, this theory is very suitable to be applied in learning, especially learning in Islamic Religious Education.It cannot be denied that with the advent of behavioristic theory, it has been widely used by subject teachers in fostering student behavior. Discussing related to behavior then regardless of the learning of Islamic Education (PAI) itself. As the existence of PAI learning is a subject that must be present in every school. The realization of behavior changes in students can be done by providing stimuli so as to bring up a good response. The purpose of this study is to understand the importance of applying behavioristic theories to the learning of Islamic Religious Education. The method used by the author is descriptive qualitative with data collection such as observation, interviews, and documentation. Based on the results of the study the authors found that the application of Behavioristic learning theory to the learning of PAI in Nogopuro Elementary School was quite good. It was marked by a change in positive student behavior, such as learning motivation, interactive, strengthening memory, and tolerance. The existence of behavioristic learning theories in the learning of Islamic Religious Education in Nogopuro Elementary School is familiar. The theory is considered as a proper reference material to be applied in the learning of Islamic Religious Education and it is hoped that by applying this theory it will be able to realize changes in student behavior towards better.